The effect of seasonal access and passage of motor vehicle on the air qualityin the Shchuchinsko- Borovskya zone of the Republic of Kazakhstan - Maikanov, Balgabay S.; Auteleeyva, Laura T. (Journal of the Belarusian State University. Ecology, 2020)
The analysis of the seasonal access and passage of vehicles and measurement of atmospheric air quality were carried out at four checkpoints and Abylai- khan Meadow in the Shchuchinsko-Borovskoy resort zone within three periods (cold, transitional, warm). It was found that the number of vehicles increases in the warm period (3204: 2480: 993) than in the transitional and cold periods. The standard index (2.14) and the highest repeatability (16.6%) of the warm period are characterized by a high level of sulfur dioxide pollution. The average concentration of SO2 at checkpoint No. 4 exceeds 2 MAC and amounts to 1.070 ± 0.03 mg / m3.
Keywords: Shchuchinsko-Borovskoy resort zone (ShchBRZ); atmospheric air; motor vehicle; sulfur dioxide